Post-rehabilitation programme to support upper limb recovery in community-dwelling stroke survivors: a mixed methods cluster-feasibility controlled trial - Janice J Eng; Suzanne McDonough; Gary Adamson; Katy Pedlow; Natalie Klempel; Jenny Hylands; Noelene Hughes; Zoe Campbell; Niamh C Kennedy (BMJ Open)
Background Less than 50% of stroke survivors regain their pre-stroke level of upper limb function, compounded with a lack of long-term rehabilitation options available. The Graded Repetitive Arm Supplementary Programme (GRASP) is an evidence-based upper limb programme delivered as a standalone programme to stroke survivors. To improve access to such a programme, there is the potential to combine it with a high-utility community-based exercise programme, such as the post-rehabilitation enablement programme (PREP). We aimed to establish if this was feasible to deliver alongside the experience of stroke survivors and therapists, identify any refinements the intervention and the acceptability of the intervention and trial procedures.Methods A cluster feasibility-controlled trial was conducted using both quantitative and qualitative outcome measures with stroke survivors who were discharged from NHS care. Participants completed PREP for 6 weeks (control), with the intervention group also completing GRASP. The GRASP intervention was refined in between five iterative testing cycles. Focus groups with participants explored the acceptability and feasibility. Individual interviews with intervention therapists explored how feasible it was to embed the intervention into practice, and determine the feasibility of a future larger, mixed methods, randomised controlled trial. Clinical endpoints for upper limb and overall function were explored through the Rating of Everyday Arm use in the Community and Home, 10-metre walk test (10MWT) and quality of life via the Shortened Edinburgh Warwick questionnaire. No further suggestions for intervention design were noted after cycle 4.Results Recruitment (n=72) and retention levels (84.7%) were high with 61 participants (mean age of 66 years and 49 weeks post-stroke) completing the study. Participants and therapists reported positive acceptability of the intervention with goal setting and family support noted as beneficial. The home exercise programme was noted as challenging. Participants within both groups demonstrated improvements in clinical measures, with the intervention group demonstrating a greater improvement within the Rating of Everyday Arm-use in the Community and Home and the 10MWT.Conclusion This study successfully recruited and retained stroke survivors into an upper limb community-based programme. It poses a feasible delivery mechanism to combine evidence-based upper limb approaches with established physical activity programmes in a future large scale and fully powered study.Trial registration number NCT05090163.